Analisis Materialitas pada Prosedur Audit Vouching atas Akun Beban Operasional oleh KAP DS (Jurnal Riset Manajemen dan Akuntansi, 2025)
The application of the materiality concept in the vouching audit process of operational expense accounts at Public Accounting Firm (KAP) DS plays a crucial role in enhancing the effectiveness and efficiency of the audit process. Materiality serves as a guideline for auditors in determining the threshold for significant transactions, thereby allowing the audit to focus on elements that most affect the quality of financial statement presentation. Using a qualitative descriptive approach, data was obtained through interviews, direct field observations, and document reviews. The results indicate that this approach assists auditors in selecting the appropriate transaction samples to be tested using the vouching technique. Furthermore, the procedure is also effective in revealing improper recordings, such as period errors or the absence of supporting documents. The auditor's accuracy in determining the level of materiality, along with the quality of documentation provided by the client, are key factors in the success of the audit. Thus, the use of materiality in vouching procedures has proven to enhance the reliability of the information presented in the financial statements.